The Impact of Adopting Time-of-Day Tolling Case Study of 183A in Austin, Texas - Light, Thomas (RAND Corporation, 2015)
This study evaluates the traffic and revenue impacts of moving from a fixed toll rate on the 183A Turnpike in Texas to a toll structure that varies by time of day. RAND administered a stated preference survey and developed discrete choice models to understand how motorists are likely to respond to alternative tolling arrangements. Shifting to time-of-day tolling is not likely to reduce congestion downstream in the transportation network.